Genome-Wide Identification and Transcript Analysis Reveal Potential Roles of Oligopeptide Transporter Genes in Iron Deficiency Induced Cadmium Accumulation in Peanut - Wang, Chaohui; Wang, Xueqin; Li, Jinxiu; Guan, Junhua; Tan, Zengjing; Zhang, Zheng; Shi, Gangrong (Frontiers in Plant Science, 2022)
The oligopeptide transporter (OPT) family is a group of proton-coupled symporters that play diverse roles including metal homeostasis. However, little is known about this family in peanut. To reveal potential roles of AhOPT genes in Fe/Cd interactions, peanut AhOPT genes were genome-widely identified, and the relationships between gene expression and Cd accumulation were detected in two contrasting peanut cultivars (Fenghua 1 and Silihong) under Fe-sufficient or Fe-deficient conditions. A total of 40 AhOPT genes were identified in peanut, which were divided into two subfamilies (PT and YS). Most AhOPT genes underwent gene duplication events predominated by whole-genome duplication. Clustered members generally have similar protein structures. However, gene structural divergences occurred in most of the duplicated genes. Transcription analysis revealed that AhOPT3.2/3.4 and AhYSL3.1/3.2 might be responsible for Fe deficiency tolerance, while AhOPT3.1/3.4, AhOPT7.1/7.2, and AhYSL1.1 be involved in Fe/Cd interactions. These genes might be regulated by transcription factors including ATHB-12, ATHB-6, DIVARICATA, MYB30, NAC02, DOF3.4, IDD7 and LUX. Reduced expressions of AhYSL3.1/3.2 and higher expression of AhOPT3.4 might contribute to higher Fe-deficiency tolerance in Silihong. Higher expression of AhOPT7.3 and AhOPT6.1 might be responsible for low Cd accumulation in Fenghua 1. Our results confirmed that AhOPT3/6/7 and AhYSL1/3 might be involved in the transport of Fe and/or Cd in peanut and provided new clues to understanding potential mechanisms of Fe/Cd interactions.